Innovative Research on Ethnic Music Performance Models in Southwestern Chinese Universities under Digital Technology - Huan, LinYa; Jirajarupat , Phakamas; Liu , LingLing (Journal of Roi Kaensarn Academi, 2024)
This research mainly involves the innovation of folk music performance in universities in southwest China under digital technology. The research samples selected the Music Digital Performance Laboratory of Yunnan Minzu University and the integration course of folk music and Digital technology of Guizhou Minzu University as cases. The research tools mainly include the literature analysis method, the case analysis method, and the interview method. In terms of data collection, data on the integration of digital technology and folk music performance were collected through the sorting out of relevant literature, field visits and interviews with relevant personnel. In terms of research and analysis, this research discusses the influence of digital technology on folk music performance in universities from the perspectives of cultural inheritance and protection, education and teaching, art innovation and development, and puts forward corresponding innovative countermeasures and suggestions for the existing problems. Through the research on the innovation of folk music performance in universities in southwest China, we find that the integration of digital.